Contemporary considerations in adjuvant radioiodine treatment of adults with differentiated thyroid cancer. Issue 9 (9th May 2020) - Juweid, Malik E.; Tulchinsky, Mark; Mismar, Ayman; Momani, Munther; Zayed, Ayman A.; Al Hawari, Hussam; Albsoul, Nader; Mottaghy, Felix M.
Abstract: Differentiated thyroid cancer (DTC) is the most common endocrine malignancy with a growing incidence worldwide. The initial conventional management is surgery, followed by consideration of 131 I treatment that includes three options. These are termed remnant ablation (targeting benign thyroid remnant), adjuvant (targeting presumed microscopic DTC) and known disease (targeting macroscopic DTC) treatments. Some experts mostly rely on clinicopathologic assessment for recurrence risk to select patients for the 131 I treatment. Others, in addition, apply radioiodine imaging to guide their treatment planning, termed theranostics (aka theragnostics or radiotheragnostics). In patients with low‐risk DTC, remnant ablation rather than adjuvant treatment is generally recommended and, in this setting, the ATA recommends a low 131 I activity. 131 I adjuvant treatment is universally recommended in patients with high‐risk DTC (a primary tumor of any size with gross extrathyroidal extension) and is generally recommended in intermediate‐risk DTC (primary tumor >4 cm in diameter, locoregional metastases, microscopic extrathyroidal extension, aggressive histology or vascular invasion). The optimal amount of 131 I activity for adjuvant treatment is controversial, but experts reached a consensus that the 131 I activity should be greater than that for remnant ablation. The main obstacles to establishing timely evidence through randomized clinical trials for 131 I therapy include years‐to‐decades delay in recurrence and low disease‐specific mortality. This mini‐review is intended to update oncologists on the most recent clinical, pathologic, laboratory and imaging variables, as well as on the current 131 I therapy‐related definitions and management paradigms, which should optimally equip them for individualized patient guidance and treatment.